ABR797: Applied Business Research - MIBF I / Arshad Ayub Graduate Business School - UiTM, Arshad Ayub Graduate Business School (Universiti Teknologi MARA (UiTM), 2018)
This course will provide a platform in understanding the role of BUSINESS research in shaping decision. This specialized course covers topics such as the nature of research, business problem, research design, theoretical framework, scales and measurement , questionnaire design, sampling design and procedures, data collection methods and field, data processing, analysis and interpretations, hypothesis testing, research proposal and presentation of research report.